A two-center randomized controlled trial of water-aided colonoscopy versus air insufflation colonoscopy - Cadoni, Sergio; Gallittu, Paolo; Sanna, Stefano; Fanari, Viviana; Porcedda, Maria L.; Erriu, Matteo; Leung, Felix W. (Endoscopy, 2014)
Background and study aim: Water-aided colonoscopy includes water immersion and water exchange. Several small single-center studies have suggested that the use of water rather than air insufflation during colonoscopy reduces pain on insertion. The aim of this study was to investigate whether water-aided colonoscopy is less painful than air insufflation in a large cohort of patients.Patients and methods: This was a two-center, randomized controlled trial. Consecutive patients who agreed to start colonoscopy without premedication were included. Sedation was administered on demand. Water-aided colonoscopy was performed using water immersion in the early phase of the study, and subsequently water exchange was used. The primary endpoint was cecal intubation with pain scores of ≤ 2 and sedation with no or ≤ 2 mg midazolam. Secondary outcomes were pain score at discharge, cecal intubation rate and time, and adenoma detection rate (ADR).Results: A total of 672 patients were randomized to water exchange (n = 338) or air insufflation (n = 334). The primary endpoint was achieved in more patients in the water exchange group (83.8 % vs. 62 %; P < 0.0005). On-demand sedation was also required less (11.5 % vs. 26.0 %; P < 0.0005) and mean pain score was lower (1.3 vs. 2.3; P < 0.0005) in the water exchange group. The cecal intubation rates were comparable. Water exchange had a significantly higher overall ADR (25.8 % vs. 19.1 %; P = 0.041), proximal ADR (10.1 % vs. 4.8 %; P = 0.014), and proximal < 10 mm ADR (7.7 % vs. 3.9 %; P = 0.046); proximal ADR was also higher in screening-only patients in the water exchange group (18.9 % vs. 7.4 %; P  = 0.015). No detailed analysis was possible for the air insufflation vs. water immersion comparison.Conclusion: The current results confirmed that water exchange minimized the requirement for sedation and increased the ADR.